1986
DOI: 10.1007/bf01907429
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences in the resistance of rats to isoprenaline-induced heart lesions

Abstract: Two strains of rats were obtained by selective breeding: the IR strain, resistant to isoprenaline-induced myocardial lesions and the IS strain, sensitive to this damage. The IR rats grew more slowly, the weight of their adipose tissue was higher and the weight of m. soleus was less than that of the IS rats. The IR rats had a higher content of triglycerides in the serum and a lower isoprenaline-stimulated lipolytic activity of adipose tissue in vitro. The basal NEFA level in the serum and its rise after the adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Mráz et al (1995) demonstrated a significant increase in heart glycogen after daily injection of isoprenaline. Other papers (Faltová et al 1983a & b;Mráz et al 1986) demonstrated that a long administration of prolonged stressors like starvation also led to an increase of glycogen and decrease of cardiac damage. Glycogen certainly plays a positive and protective role for myocard.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Mráz et al (1995) demonstrated a significant increase in heart glycogen after daily injection of isoprenaline. Other papers (Faltová et al 1983a & b;Mráz et al 1986) demonstrated that a long administration of prolonged stressors like starvation also led to an increase of glycogen and decrease of cardiac damage. Glycogen certainly plays a positive and protective role for myocard.…”
Section: Discussionmentioning
confidence: 92%
“…Heart lesions after 1 mg ¡ kg ª1 of isoprenaline (accumulation index of 203 Hg) more less Mráz et al (1986) Heart lesions after water immersion restraint stress (accumulation index of 203 Hg) more less Starec et al (1994) Gastric ulcers after water immersion restraint stress (ulcer index) less more Starec et al (1994) Heart glycogen less more Mráz et al (1995) Severity of adjuvant arthritis less more Starec et al (1994) Open field -walking less more Rasková et al (1996) Open field -freezing more less Rasková et al (1996) Aggressive behaviour -intruder test less more Starec et al (1994) behavioural and pathophysiological differences observed were established repeatedly during different seasons of the year (Mráz et al 1995;Rasková et al 1996;Starec et al 1996).…”
Section: Observed Characteristics Is Ir Referencementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, energy metabolism differs considerably in animals with different degrees of resistance. For example, the glycogen content is much higher in the myocardium of rats with high resistance to isoproterenol than in rats with low resistance to it [14]. The NADH-oxidase pathway is the major source of reducing equivalents of the oxidation chain in LR rats, while in HR rats it is the succinate oxidase pathway [5].…”
Section: Comparison Of Lpo Parameters In Wistar Rats Differing In Resmentioning
confidence: 99%
“…For all measurements animals were killed by decapitation. Isoprenaline-sensitive rats (IS) react to application of isoprenaline with large myocardial lesions, whereas the rats resistant to isopr~naline (IR) have significantly smaller myocardial defects (Mraz et al 1986). Acute stress evokes heart pathology in the IS strain to the same extent as isoprenaline, but it induces gastric lesions in IR rats.…”
Section: Department Of Normal Pathological and Clinicalmentioning
confidence: 99%